LOYALITAS MASYARAKAT JAWA KUNO KEPADA RAJA BERDASARKAN DATA PRASASTI ABAD XIII–XV MASEHI - Geraldine, Victoria; Rahayu, Andriyati (UI Scholars Hub, 2024)
The sima inscription is an edict issued by the king as a gift given to certain parties. One of the reasons for its bestowment is as a reward to those who have shown him loyalty. This paper studies the forms of loyalty shown by the Ancient Javanese People to the king and the factors that influenced it. The study aims to give an understanding of the relationship that existed between the Ancient Javanese people and the king in the XIII–XV Centuries AD. The results of this research provides new insight for the effort to reconstruct the life of the Ancient Javanese people. The method used in this study consists of data collection, data analysis, and interpretation. Based on this series of studies, it can be determined that there are multiple forms of loyalties shown by the Ancient Javanese people to the king and multiple factors that influenced its formation.